2014
DOI: 10.2147/ijwh.s38969
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture and women's health: an overview of the role of acupuncture and its clinical management in women's reproductive health

Abstract: BackgroundAcupuncture and other modalities of Chinese/East Asian medicine have been used to treat women’s health for many centuries. Gynecology specialties focus particularly on menstrual and reproductive disorders. Both the adoption of the use of acupuncture outside Asia, and the incorporation of scientific analysis in Asia have challenged biomedical conceptions of what can be achieved with this treatment method. The scale of research activity in relation to acupuncture and women’s health has increased over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 82 publications
0
23
0
Order By: Relevance
“…8 Empirical evidences suggests that acupuncture can enhance women's reproductive functioning and mitigative fertility issues. 9 Naturopathy is a wholesome approach intended to heal the underlying cause by averting the root cause of the disease. It also provides a healthy internal environment to the body to accelerate its healing mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…8 Empirical evidences suggests that acupuncture can enhance women's reproductive functioning and mitigative fertility issues. 9 Naturopathy is a wholesome approach intended to heal the underlying cause by averting the root cause of the disease. It also provides a healthy internal environment to the body to accelerate its healing mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…A narrative literature research explored the literature up to June 2013 on acupuncture and its mechanism of action and its use and impact on female reproductive disorders (Cochrane et al, 2014). The synthesis demonstrated that data extracted from 204 papers provided clinical data which indicated that acupuncture may improve menstrual problems and women's abilities to fall pregnant.…”
Section: Evidence Base For Acupuncture and Female Reproductive Disordersmentioning
confidence: 99%
“…The release of neurotransmitters-such as dopamine, serotonin, neuropeptides, and oxytocin-might be initiated by acupuncture, which, in turn, could influence the hypothalamus-pituitary-ovarian axis to promote ovulation, regulate menses, and increase overall fertility. 12,14 In polycystic ovary syndrome, acupuncture could affect glucose uptake in the skeletal tissue, 15,16 might decrease hyperinsulinemia, and might increase insulin clearance. 17 The aim of this article is to provide an overview of the current literature evaluating acupuncture's effects on IVF outcomes.…”
Section: Introductionmentioning
confidence: 99%